Characterization of the effects on pruritus by novel treatments for atopic dermatitis. (27th December 2021) - Bonnekoh, Hanna; Butze, Monique; Metz, Martin
Summary: Chronic pruritus is a common and debilitating symptom in patients with atopic dermatitis and contributes to impairment of quality of life. Effective treatment of pruritus should therefore be one of the main treatment goals in patients with atopic dermatitis. Pathophysiologically, the histamine‐independent pruritogens interleukin‐31, interleukin‐13, and interleukin‐4, have been shown to play a major role in atopic dermatitis. All three cytokines can mediate chronic pruritus via Janus kinase 1/2 signaling pathways. Novel drugs target these pathways and have shown rapid and sustained reduction of pruritus in patients with atopic dermatitis in clinical use and in phase II and III clinical trials. Here we summarize the published data on the effects of these drugs on itch parameters such as overall reduction in pruritus intensity and percent of patients with atopic dermatitis achieving a relevant reduction in itch. Each of the novel drugs shows very good effects on pruritus. These data offer hope for an even better and possibly more specific treatment of pruritus in patients with atopic dermatitis in the future. In addition, the different pharmacological approaches give us the chance to learn more about the pathophysiology of pruritus in atopic dermatitis.